INTERACTIVE METHODS OF TEACHING MULTIPLICATION TO PRIMARY EDUCATION STUDENTS (Scientific journal of the Fergana State University, 2025)
This article examines the effectiveness of using interactive methods in teaching multiplication. Different from traditional approaches, ways to increase students' interest in the lesson through didactic games, visual materials and modern technologies are analyzed. The impact of interactive methods on strengthening mathematical concepts and developing students' creative thinking is studied, and practical recommendations are presented.